Syk signaling in dendritic cells orchestrates innate resistance to systemic fungal infection. - Paul G Whitney; Eva Bär; Fabiola Osorio; Neil C Rogers; Barbara U Schraml; Safia Deddouche; Salomé LeibundGut-Landmann; Caetano Reis e Sousa (PLoS Pathogens)
Host protection from fungal infection is thought to ensue in part from the activity of Syk-coupled C-type lectin receptors and MyD88-coupled toll-like receptors in myeloid cells, including neutrophils, macrophages and dendritic cells (DCs). Given the multitude of cell types and receptors involved, elimination of a single pathway for fungal recognition in a cell type such as DCs, primarily known for their ability to prime T cell responses, would be expected to have little effect on innate resistance to fungal infection. Here we report that this is surprisingly not the case and that selective loss of Syk but not MyD88 in DCs abrogates innate resistance to acute systemic Candida albicans infection in mice. We show that Syk expression by DCs is necessary for IL-23p19 production in response to C. albicans, which is essential to transiently induce GM-CSF secretion by NK cells that are recruited to the site of fungal replication. NK cell-derived-GM-CSF in turn sustains the anti-microbial activity of neutrophils, the main fungicidal effectors. Thus, the activity of a single kinase in a single myeloid cell type orchestrates a complex series of molecular and cellular events that underlies innate resistance to fungal sepsis.